PENGARUH PENEMPATAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. VALANTA BANYUASIN - Herman Efrizal; S Suharti (JURNAL KOMPETITIF, 2020)
The Effect of Work Placement and Compensation on Employee Performance at PT. Valanta Banyuasin.Population of 32 employees. Sample 32 people. Data techniques by means of interviews, observation and surveys. Descriptive analysis techniques, multiple linear regression analysis, free coefficient analysis (r), and coefficient of determination (r2). The data analysis requirements test used the classical assumption test consisting of multicollinearity, heteroscedasticity and autocorrelation. As for the accepted hypothesis, the t test (partial) and F test (simultaneous).This study shows the coefficient of determination (R2) of 0.976 or 97.6%, which means that employee performance variables can be applied by job placement variables and compensation compensation by other factors such as motivation, leadership, training, work environment and organizational culture. Job placement variables and simultaneously have a significant positive effect on employee performance.Keywords:  Job Placement, Compensation, Employee Performance